Acceleration in germination sensu stricto plays a central role on seedling vigor in post-germination - Ribeiro-Oliveira, João Paulo; Bosseli, Marco Aurélio; da Silva, Edvaldo Aparecido Amaral [UNESP] (MDPI, 2021)
An obvious relationship between germination sensu stricto and seedling development during post-germination has been considered, but not explained concerning vigor. Taking this into account, we used measurements of water dynamics in germinating seeds and seedling development to clarify that relationship. The biological model was soybean seeds, since it is the most relevant ‘true seed’ produced around world. Our findings suggest that the way energy is used (acceleration) and not its input (velocity) is the main aspect relating seed germination and seedling development, especially when considering vigor. However, velocity and acceleration can be complementary in analyses of seed physiology. Other measurements proposed here also have potential uses for testing vigor in seed lots, such as seedling vigor index and biological activity in the lot. Therefore, water dynamics in germinating seeds can be an interesting way for testing seed lots, because it is an easier, faster and cheaper method in relation to other non-destructive procedures.
Keywords: Acceleration; Biological activity; Germination measurements; Imbibition; Indexes; Seed physiology; Soybean; Velocity